Sequential Ligand-Dependent Notch Signaling Activation Regulates Valve Primordium Formation and Morphogenesis. Issue 10 (13th May 2016) - MacGrogan, Donal; D'Amato, Gaetano; Travisano, Stanislao; Martinez-Poveda, Beatriz; Luxán, Guillermo; del Monte-Nieto, Gonzalo; Papoutsi, Tania; Sbroggio, Mauro; Bou, Vanesa; Gomez-del Arco, Pablo; Gómez, Manuel Jose; Zhou, Bin; et al.
Abstract : Rationale: : The Notch signaling pathway is crucial for primitive cardiac valve formation by epithelial–mesenchymal transition, and NOTCH1 mutations cause bicuspid aortic valve; however, the temporal requirement for the various Notch ligands and receptors during valve ontogeny is poorly understood. Objective: : The aim of this study is to determine the functional specificity of Notch in valve development. Methods and Results: : Using cardiac-specific conditional targeted mutant mice, we find that endothelial/endocardial deletion of Mib1-Dll4-Notch1 signaling, possibly favored by Manic-Fringe, is specifically required for cardiac epithelial–mesenchymal transition. Mice lacking endocardial Jag1, Notch1, or RBPJ displayed enlarged valve cusps, bicuspid aortic valve, and septal defects, indicating that endocardial Jag1 to Notch1 signaling is required for post–epithelial–mesenchymal transition valvulogenesis. Valve dysmorphology was associated with increased mesenchyme proliferation, indicating that Jag1-Notch1 signaling restricts mesenchyme cell proliferation non–cell autonomously. Gene profiling revealed upregulated Bmp signaling in Jag1 -mutant valves, providing a molecular basis for the hyperproliferative phenotype. Significantly, the negative regulator of mesenchyme proliferation, Hbegf, was markedly reduced in Jag1 -mutant valves. Hbegf expression in embryonic endocardial cells could be readily activated through a RBPJ-binding site, identifying Hbegf as an endocardial Notch target. Accordingly, addition of soluble heparin-binding EGF-like growth factor to Jag1 -mutant outflow tract explant cultures rescued the hyperproliferative phenotype. Conclusions: : During cardiac valve formation, Dll4-Notch1 signaling leads to epithelial–mesenchymal transition and cushion formation. Jag1-Notch1 signaling subsequently restrains Bmp-mediated valve mesenchyme proliferation by sustaining Hbegf-EGF receptor signaling. Our studies identify a mechanism of signaling cross talk during valve morphogenesis involved in the origin of congenital heart defects associated with reduced NOTCH function. Abstract : Supplemental Digital Content is available in the text.